2018
DOI: 10.3390/brainsci8050087
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Automatized Naming, Verbal Working Memory, and Rhythm Discrimination as Predictors of Reading in Italian Undergraduate Students with and without Dyslexia

Abstract: Whereas the clinical manifestations and the neuropsychological predictors of Developmental Dyslexia (DD) are already well documented in Italian-speaking children, empirical evidence on DD in Italian adults is in contrast rather scarce. The aim of the present study was to investigate the role of a subset of neuropsychological skills, which have been identified by previous literature to be related to reading, in the decoding abilities of a group of Italian undergraduates with and without DD. For this purpose, 39… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 48 publications
1
10
0
1
Order By: Relevance
“…Further studies conducted with Italian children (i.e., 6- to 11-years-old; Di Filippo et al., 2005) and young adults (i.e., 19- to 27-years-old; Cancer & Antonietti, 2018) with dyslexia suggest that phonological awareness and serial rapid automatized naming (RAN) deficits are the strongest factors accounting for reading performance ─ an effect being found across many languages (for a review see Norton & Wolf, 2012) ─ since they ‘predict different portions of variance in reading tasks’ (Di Filippo et al., 2005, p. 350). Overall, in RAN tasks phonological skills are engaged automatically (i.e., implicit phonological processing, see Melby-Lervåg et al., 2012), since participants access phonological codes without any awareness, in order to name (i.e., retrieve from a lexical knowledge system) rapidly sequences of visually presented stimuli (e.g., objects, colors).…”
mentioning
confidence: 99%
“…Further studies conducted with Italian children (i.e., 6- to 11-years-old; Di Filippo et al., 2005) and young adults (i.e., 19- to 27-years-old; Cancer & Antonietti, 2018) with dyslexia suggest that phonological awareness and serial rapid automatized naming (RAN) deficits are the strongest factors accounting for reading performance ─ an effect being found across many languages (for a review see Norton & Wolf, 2012) ─ since they ‘predict different portions of variance in reading tasks’ (Di Filippo et al., 2005, p. 350). Overall, in RAN tasks phonological skills are engaged automatically (i.e., implicit phonological processing, see Melby-Lervåg et al., 2012), since participants access phonological codes without any awareness, in order to name (i.e., retrieve from a lexical knowledge system) rapidly sequences of visually presented stimuli (e.g., objects, colors).…”
mentioning
confidence: 99%
“…Studies show that PA-based instructions and instruments significantly improve reading and/or vocabulary skills in various languages: English (Huo & Wang, 2017), Italian (Cancer & Antonietti, 2018), German (Degé & Schwarzer, 2011), French (Martin et al, 2010), Portuguese (Gottardo, Pasquarella, Chen, & Ramirez, 2016), Spanish (Páez & Rinaldi, 2006), and Chinese (Wang, 2017). A few studies investigated the contributions of PA-based instructions and instruments to Arabic-reading scores.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Besides reading, RAN is assessed using the RAN test (De Luca et al, 2005), which was found to be a strong predictor of reading difficulties in older individuals (Cancer and Antonietti, 2018a). In this test, participants are required to sequentially name various visual stimuli (i.e., colored squares, black and white icons, and numbers) presented in 10 × 5 matrices.…”
Section: Behavioral Measuresmentioning
confidence: 99%